Depressive symptoms and use of HIV care and medication-assisted treatment among people with HIV who inject drugs. (1st March 2021) - Zeziulin, Oleksandr; Mollan, Katie R.; Shook-Sa, Bonnie E.; Hanscom, Brett; Lancaster, Kathryn E.; Dumchev, Kostyantyn; Go, Vivian F.; Chu, Viet A.; Kiriazova, Tetiana; Syarif, Zulvia; Dvoryak, Sergii; Reifeis, Sarah A.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Vietnam, Indonesia, and Ukraine have major burdens of IDU and HIV. We estimated the prevalence of depressive symptoms at baseline among people living with HIV who inject drugs, evaluated associations between depression at baseline and 12-month HIV care outcomes and medication-assisted treatment (MAT), and evaluated the study intervention effect by baseline depression subgroups. Design: HPTN 074 was a randomized study. The study intervention included psychosocial counseling, systems navigation, and antiretroviral treatment (ART) at any CD4 + cell count. Methods: Moderate-to-severe depression was defined as a Patient Health Questionnaire-9 score of 10 or above. ART and MAT were self-reported. Eligibility criteria were: 18–60 years of age, active IDU, and viral load of at least 1000 copies/ml. Adjusted probability differences (aPD) were estimated using inverse-probability weighting. Results: A total of 502 participants enrolled from April 2015 to June 2016. Median age was 35 years; 85% identified as men. Prevalence of baseline moderate-to-severe depression was 14% in Vietnam, 14% in Indonesia, and 56% in Ukraine. No evident associations were detected between baseline depression and ART, viral suppression, or MAT at 12-month follow-up. The study intervention improved the proportions of people who inject drugs achieving 12-month viral suppression in both the depressed [intervention 44%; standard of care 24%; estimated aPD = 25% (95% confidence interval: 4.0%, 45%)] and nondepressed subgroups [intervention 38%; standard of care 24%; aPD = 13% (95% confidence interval: 2.0%, 25%)]. Conclusion: High levels of depressive symptoms were common among people living with HIV who inject drugs in Ukraine but were less common in Vietnam and Indonesia. The study intervention was effective among participants with or without baseline depression symptoms.